The effect of drip irrigation on the productivity of white cabbage - Nurmatov N.J.; Alibekov T (Zien Journals, 2023)
Productivity is the result of biological and biophysical processes that take place in a plant depending on its genetic characteristics and external environmental factors
Keywords: White cabbage; cabbage; limited field moisture capacity